Robot‐assisted partial nephrectomy is associated with early recovery of renal function: Comparison of open, laparoscopic, and robot‐assisted partial nephrectomy using DTPA renal scintigraphy. Issue 7 (28th February 2019) - Choi, Se Young; Jung, Han; You, Dalsan; Jeong, In Gab; Song, Cheryn; Hong, Bumsik; Hong, Jun Hyuk; Ahn, Hanjong; Kim, Choung‐Soo
Abstract: Objectives: To compare the functional outcomes of open, laparoscopic, and robot‐assisted partial nephrectomy (OPN, LPN, and RAPN, respectively) using diethylene triamine penta‐acetic acid (DTPA). Methods: We identified 610 patients who underwent partial nephrectomy for renal cell carcinoma (285 open partial nephrectomy [OPN], 96 laparoscopic partial nephrectomy [LPN], and 229 robot‐assisted partial nephrectomy [RAPN]) with preoperative and postoperative DTPA within 1 year. We excluded multiple renal masses and history of immunotherapy or chemotherapy. Predictive factors for glomerular filtration rate (GFR) reduction were assessed using multivariate linear regression. Results: Postoperative complications and disease‐free survival were similar in the three groups. Within 1 postoperative year, OPN showed a significantly lower mean ipsilateral GFR than LPN and RAPN (28.9 versus 32.4 versus 32.7 mL/min/1.73 m 2, respectively; P  < 0.001). RAPN was associated with a significantly higher total GFR than OPN within 1 year (76.6 versus 71.2 mL/min/1.73 m 2, respectively; P  = 0.001). On multivariate analysis within 1 year, operation type (OPN versus RAPN: β = 2.82; 95% confidence interval, 1.17–4.48; P  = 0.001) was significantly associated with GFR reduction. Conclusion: There was no difference in postoperative complications and disease‐free survival among operation types. RAPN could help to promote earlier recovery of ipsilateral GFR than OPN.